PENGARUH CAPITAL STRUCTURE TERHADAP FIRM VALUE DENGAN PROFITABILITY SEBAGAI VARIABEL INTERVENING - Anisa Anisa (Jurnal Riset Entrepreneurship, 2020)
The aim of this study was to test the effect of capital structure on firm value. Meanwhile, ‘profitability’ served as the mediating variable on the mining companies which have been go public and registered in Indonesia Stock Exchange. This study belonged to quantitative research and it was expected to successfully measure the effects between the variables. Data collection was performed by using secondary data from the official website of Indonesia Stock Exchange (BEI), which is IDX, related to the 21 mining companies registered in BEI, of which these companies achieved profits in a period of three years (2016, 2017 and 2018). Data processing was performed by using a program so-called Smart Pls 3.0. The first result of this study implied that the variable namely ‘profitability’ was the one that partially mediated the effect of the capital structure on the firm value. The second result was that no direct effect was found between capital structure and firm value. As for the next research result, profitability has no impact on the firm value. The companies with the ever growing risks would lead the creditor to increase the interest rates, resulting in the increment of the company’s average capital costs. The companies who possessed big amount of debts tended to had higher average capital costs so the values of the companies were rather falling off. Keywords : capital structure, firm value, profitability